The Wadden Sea, a gigantic world natural heritage park (Bulletin KNOB, 2011)
Since 2009 the Dutch and German parts of the Wadden Sea have been on the Unesco list of world heritage. Germany and - on an international level - the Wadden Sea Forum and the Common Wadden Sea Secretariat in Willemshaven promote the idea to experience the Wadden Sea as a gigantic North European nature park, from the islands to the continental coast. The Netherlands pursue a policy which has so far adopted a reserved attitude towards the concept of a gigantic park. As a result, since 2009 not a single additional tourist came to experience mudflats from the Dutch coast in the special setting offered by the Wadden Sea (the light, the seals and the brooding birds). A history is at the root of the Dutch reserve, and nevertheless the northern provinces are trying to design a new chapter with the aid of the national 'Waddenfonds' (Wadden Sea Fund), with more attention and possibilities for experiencing the mudflats.The history of this reserved attitude is as follows: In the 70s of the 20th century the intention still was to reclaim all the summer polders, tidal marshes and mudflats of the province of Friesland (the western edge of the Dutch Wadden Sea), which had formed in the course of centuries. The plan was abandoned in 1979. Thus the 'Dutch Society for the Preservation of the Wadden Sea', founded in 1965, was confirmed in its role of pioneer. In 2004 the government combined the aim of preservation with the extraction of natural gas in the Wadden Sea, whereby a fund was created - the 'Waddenfonds' - for scientific research and practical measures for the stabilization of the economy and the natural balance in the Wadden Sea area, also in view of the approaching climate change. In line with this policy 'nature compensation' - in areas lying inside the dikes - was introduced as a measure taken in connection with the harbour activities and energy production in Eemshaven. The National Park locations for an explicit experience of nature related to mudflats are limited to two islands (Texel and Schiermonnikoog), and Lauwersmeer, which is not connected with the Wadden Sea.In Germany, just as in Denmark, the entire Wadden Sea is National Park. In the Netherlands access to the area outside the dikes is formally prohibited, with the exception of a limited number of coastal locations (for guided walks across the mudflats and birdwatching), whereas in Germany the National Park is much used by tourists on small artificial beaches and nature lovers in the tidal marshes. The Dutch policy stimulates new forms of creating mudflats and bird-observation locations in areas within the dikes (Emmapolder). With considerable subsidy from the Waddenfonds this phenomenon is being expanded at the moment. The Frisian provincial nature association 'It Fryske Gea' has realized a mudflats centre next to the dike near Hallum, which is to be opened in 2012. The association is counting on fifteen to twenty thousand visitors to the mudflats centre a year. The province of Groningen is going to lay out a cycle track alternately on and next to the dike, on locations where there is no cycle track yet, so that a long cycling tour along the Wadden Sea will be possible in 2015. These small-scale interventions along and on the large-scale sea wall will transform it into a multifunctional dike: a jewel consciously framing a world natural heritage relating a Dutch mentality to the Wadden Sea in a recognizable way, for both Dutch and foreign tourists.